An exploration of live experiences of Balik-Islam using interpretative phenomenological analysis. - Clamucha, Tiffany Gail C.
The primary goal of this study was to explore and gain an understanding of how Balik-Islam made sense of their worlds as converts to Islam. With Interpretative Phenomenological Analysis (IPA) as a theoretical and methodological framework, I gathered data by conducting semi-structured interviews among six converts to Islam. The data gathered were analyzed with the use of the four-step analytical process of IPA. The analysis of accounts revealed two essential experiences in the everyday lives of Balik-Islam: their genuine involvement in Islam and their inner conflict and struggle against discrimination from both Muslim and non-Muslims. For the Balik-Islam, the essence of bein a convert is living the Qur?an life. The findings of my study point to the need to address the struggles of Balik-Islam as they deal with society?s stereotypes and moral exclusion. Results also prove useful in advocating dialogue between non-Muslim majority and the Muslim minority in order to promote openness, understanding, and solidarity between the two groups.